Reading and note taking in monological and dialogical classes in the Social Sciences - Cartolari, Mónica Manuela (2013)
This qualitative study explores the uses of reading and note-taking in two pre-service teacher training Social Sciences courses. Data analysis of in-depth interviews with professors and students, class observations and course materials suggested two polar teaching styles according to how bibliography was included in the course and the presence or absence of dialogicality. In one course, the professor assumed that students should read texts on their own prerogative. As monological lectures were given, they mostly studied from their class-notes. In the other course, the professor held class discussions based on readings that took place in and outside the classroom. According to students, this prompted them to use their class-notes to re-signify and consider the relevance of the information read, with talking, reading, and note-taking contextualizing each other. The dialogical teaching style merged literacy practices and interwove them with disciplinary contents, promoting students’ active approach to meaning construction when learning.